Taxes and "Social Costs" - SUSAN STUNTZ (Tufts Archival Research Center, 2007)
Marginalia; Tobacco Institute briefing on taxes and "social costs." Discusses the background and assumptions involved in the issue. Identifies allies. Aims to "reduce reliance on tobacco excise taxes to meet social and economic objectives" by arguing that these taxes are regressive, unfair, and bad for the economy. Outlines strategies, goals, and tactics at the federal and state level. Includes cover memo from Susan Stuntz expressing disappointment in the briefing and demanding a new version.